Perancangan Fotografi Parodi Pada Budaya Populer Dalam Karakter Super Hero - Oky Mauludya; Sudrajat Sudrajat; Putri Sukmawati (ArtComm, 2022)
The birth of modernization of life has changed the perspective and pattern of people's lives, thus enabling the emergence of a new civilization, namely the consumptive and hedonic culture of life in the midst of urban society. This phenomenon has become something that is not strange to be a subject of discussion, it has even "transformed" into a new culture as a result of the existing cultural industry rulers shifting local culture and as if there is an impression of intentional destruction of the cultural order that is part of the national identity that has been established..